Emergence of Omicron third lineage BA.3 and its importance - Perumal Arumugam Desingu; K. Nagarajan; Kuldeep Dhama (2022)
classified as the fifth variant of concern 2,3 by the World Health Organization on November 26, 2021, the most mutated variant of SARS-CoV-2, has now circulated in 150 countries/territories until January 8, 2022, with 552 191 confirmed cases and causing 115 deaths. 4Omicron was recently divided into three lineages (BA.1, BA.2, and BA.3). 5 The differences between the BA.1 and BA.2 lineages are explored. 6Here we describe how these three lineages differ in their spike protein.Our study found that there were no specific mutations for the BA.3 lineage in spike protein.Instead, it is a combination of mutations in BA.1 and BA.2 spike proteins.All three lineages were first detected at approximately the same time and from the same place: BA.1 [hCoV-19/Botswana/ R40B59_BHP_3321001248/2021 (EPI_ISL_6640916) (2021-11-11) (Botswana/South East/Greater Gaborone/Gaborone)], BA.2 [